El aprendizaje a través de las competencias de DICH y DIH en la Facultad de Derecho de la Universidad de Buenos Aires : una mirada personal - Golmegna, Pablo (2020)
Learning through the competences of IHRL and IHL at the School of Law of the Universidad de Buenos Aires: a personal insight . -- Abstract: The Law School of the University of Buenos Aires participates in a series of international competitions in which a team, made up of students and led by professors, prepares to compete against other universities. This paper describes the dynamics of three of these competitions: the Inter-American Human Rights Moot Court Competition, the "Jean Pictet" International Competition on simulation and allegations in International Humanitarian Law and the Nelson Mandela World Human Rights Moot Court Competition. The objective is to present the various pedagogical techniques and devices that are developed in the selection, preparation and performance of the students selected to represent the faculty. In particular, in this type of experiences, the teaching method through the case method is particularly relevant, which with different variants, is present in the three competencies that are analyzed. This method is extended at the time of team selection in such a way that the teaching and learning of litigation techniques is not only reserved for those who are effectively selected to represent the UBA, but the objective is that the learning reach as many students as possible in the Faculty. Finally, it is emphasized that the experience of competing at an international level is only possible thanks to the resources that the UBA provides, which transforms the good results that have been achieved into an academic achievement of the entire institution.